Electrical and magneto-transport properties of magneto-resistive la0.7Ca0.28Sr0.2 MnO3 prepared at different sintering temperature - Ewe, L.S; Ramli, R; Lim, K.P; Abd-Shukor, R (Universiti Kebangsaan Malaysia, 2012)
The effects of strontium doping on the electrical and magneto-transport properties of magneto resistive La0.7Ca0.28Sr0.02MnO3 at different sintering temperatures have been studied. The samples were prepared by the co-precipitation technique (COP) and sintered at 1120, 1220 and 1320 oC. XRD patterns revealed that the samples have an orthorhombic structure and the diffraction patterns can be indexed with the Pbnm space group. The insulator metal transition, TIM increased linearly from 261 K to 272 K with the increase in sintering temperature. The magnetoresistance (MR) measurements were made in magnetic fields from 0.1 to 1 T at room temperature. The percentage of MR increased with increasing of magnetic field and sintering temperature for all samples. The electrical resistivity data were fitted with several equations in the metallic (ferromagnetic) and insulator (paramagnetic) regime. The density of states at the Fermi level N(EF) and the activation energy (Ea) of electron hopping were estimated by using variable range hopping and small polaron hopping model.